HUBUNGAN FAKTOR-FAKTOR SOSIAL EKONOMI PETANI DAN TINGKAT ADOPSI INOVASI BUDIDAYA PADI DI DESA KEMBANG MERTHA, KECAMATAN DUMOGA TIMUR, KABUPATEN BOLAANG MONGONDOW - Defry Kristian Rai Wongkar; Welson M. Wangke; Agnes E. Loho; Melissa L. G. Tarore (AGRI-SOSIOEKONOMI, 2016)
The objective of the research is to determine farmer’s socio-economic characteristics, the paddy’s cultivation innovation adoption degree and the relationship between farmer’s socio-economic factors with the degree of paddy’s (Oryza sativa L.) cultivation innovation adoption in Kembang Merta Village. This research is using descriptive statistic analytic method with survey technique. The study location is taken on purpose base. Kembang Mertha Village was chosen because it is one of rice production center in Bolaang Mongondow Regency. The sample was taken from 48 people by using stratified random sampling technique based on the farmer’s rice field area. The correlation test of Rank Spearman using SPSS 17 Program is used to examine the relationship between farmer’s socio-economic factors with the degree of paddy (Oryza sativa L.) cultivation innovation adoption. Research result showed that mostly respondents have 1.1 – 2 Ha paddy field area with income about Rp. 11.000.000- Rp. 15.000.000 every planting season. Mostly respondents are 40 to 50 years old that classified as productive ages and mostly were senior school graduates. The non-formal education only once to four times a year and the cosmopolitan respondents only three times a year. The degree of Paddy (Oryza sativa L.) cultivation innovation adoption observed from paddy’s cultivation stages. The soil plowing process in median 5, planting paddy in median 5, fertilization in median 4, irrigation in median 5, the pests, diseases and weeds control in median 5 and harvest and post-harvest in median 5. Correlation test indicated that land area, income, formal education and cosmopolitan level are significant to rice cultivation innovation adoption, whereas non-formal education and ages indicated insignificant relation to rice cultivation innovation adoption. *jnd